2005
DOI: 10.1136/bjsm.2004.014340
|View full text |Cite
|
Sign up to set email alerts
|

Role of exercise stress test in master athletes

Abstract: Background: The effectiveness of cardiovascular screening in minimising the risk of athletic field deaths in master athletes is not known. Objective: To evaluate the prevalence and clinical significance of ST segment depression during a stress test in asymptomatic apparently healthy elderly athletes. Methods: A total of 113 male subjects aged over 60 were studied (79 trained and 34 sedentary); 88 of them (62 trained and 26 sedentary) were followed up for four years (mean 2.16 years for athletes, 1.26 years for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
5
29
2
1
Order By: Relevance
“…Pigozzi, showed the skill level of athletes is an important factor for control of competitive state anxiety [7]. The research [8] confirmed that elite athletes have lower levels of competitive state anxiety than non-elite athletes.…”
Section: Introductionsupporting
confidence: 48%
“…Pigozzi, showed the skill level of athletes is an important factor for control of competitive state anxiety [7]. The research [8] confirmed that elite athletes have lower levels of competitive state anxiety than non-elite athletes.…”
Section: Introductionsupporting
confidence: 48%
“…Although the beneficial effect of physical exercise on cardiovascular function and health is well known, the lack of studies in older subjects raises some questions about cardiovascular function and the nature of LVH after longterm practice of competitive sports [10][11][12][13]. Regarding diastolic function, the pattern of mitral inflow has been considered an extremely important parameter to identify the nature of hypertrophy.…”
Section: Discussionmentioning
confidence: 97%
“…Although standard Doppler echocardiography has been widely used to distinguish the athlete's heart from pathologic LVH, few echocardiographic reports have defined changes in the right ventricle induced by training and related them to changes induced by LV adaptation [4][5][6]. In addition, conflicting data have been reported about the nature (physiologic vs. pathologic) of LVH in master athletes and veterans [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Such false positive results may be associated with conditions that lead to increased left ventricular mass, pressure and/or volume overload, or greater oxygen requirements, resulting in a supply demand imbalance which can decrease blood flow to the subendocardium [26]. In addition, certain clinical situations, medications, sympathetic nerve stimulation, electrolyte abnormalities, or metabolic changes may affect the STsegment at increasing heart rates resulting in false positive results [22,[27][28][29].…”
Section: Causes Of a False Positive Tetmentioning
confidence: 99%